Maritime emergency preparedness resources in the Arctic : capacity challenges and the benefits of crossborder cooperation between Norway, Russia, Iceland and Greenland : MARPART Project Report 4 - Andreassen, Natalia; Borch, Odd Jarl; Schmied, Johannes (Nord university, 2018)
This report provides an overview of maritime emergency preparedness capacities in Arctic Norway, Russia, Iceland and Greenland. It also discusses capacity challenges and the benefits of cross-border cooperation between Arctic regions.